Notes on the Ibadi religious architecture: A comparative study of the mosques in Mzab, Djerba, and Oman / Naima Benkari - Benkari, Naima (2017)
The Ibadis, like other Muslim communities, developed a rich theological literature much of which was reflected in their lifestyle - and in their architecture. This article addresses Ibadi religious architecture in the four major regions where this community has settled since the ninth century: Oman, the M'zab valley in Algeria, the island of Djerba in Tunisia and Jebel Nafusa in Libya. These mosques are distinguished from the so-called classical style of mosques by a number of characteristics. This architecture is plural in its spatial organization, volume, materials and techniques of construction, and presents a sort of air de famille that relates all its buildings to their Arab-Berber origins and Ibadi principles. These principles were generally expressed through the regulations governing construction generated by religious doctrine. This study examines some unique examples of traditional Ibadi mosques. It aims to establish that the religious texts developed by this school of thought do contain a number of opinions that have influenced the constructive traditions of the Ibadi community. It also reveals the instances where these regulations have been countered and tries to understand and interpret these cases in the light of the historical development of this community and the principles of its doctrine.